2008
DOI: 10.1002/jcb.21772
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol causes COX‐2‐ and p53‐dependent apoptosis in head and neck squamous cell cancer cells

Abstract: Cyclooxygenase-2 (COX-2) content is increased in many types of tumor cells. We have investigated the mechanism by which resveratrol, a stilbene that is pro-apoptotic in many tumor cell lines, causes apoptosis in human head and neck squamous cell carcinoma UMSCC-22B cells by a mechanism involving cellular COX-2. UMSCC-22B cells treated with resveratrol for 24 h, with or without selected inhibitors, were examined: (1) for the presence of nuclear activated ERK1/2, p53 and COX-2, (2) for evidence of apoptosis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 38 publications
2
104
1
Order By: Relevance
“…Mechanistically, it has been proposed that the anticancer effect of ASA is mediated through COX-dependent 36,37,57,58 and -independent pathways. 53,54,59 Recent studies have shown that MCF-7 mammospheres are insensitive to the cyclooxygenase pathway, and the COX-2 inhibitor (Indomethacin) was unable to reduce the mammosphere-forming capacity of MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, it has been proposed that the anticancer effect of ASA is mediated through COX-dependent 36,37,57,58 and -independent pathways. 53,54,59 Recent studies have shown that MCF-7 mammospheres are insensitive to the cyclooxygenase pathway, and the COX-2 inhibitor (Indomethacin) was unable to reduce the mammosphere-forming capacity of MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It possesses the ability to scavenge oxidatively generated free radicals, and prevents tumor progression by blocking NF-B expression, leading to cancer cell apoptosis 16,[23][24][25][26][27] . RV also has promising neuroprotective and cardioprotective effects, as well as slowing aging and delaying the onset of chronic diseases 23,[28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies have reported that resveratrol, a pharmacological inducer of COX-2, is capable of inducing p53-dependent apoptosis by implicating of COX-2 expression in a variety of cell types such as breast, thyroid, head and neck squamous cancer cells. Therefore, COX-2 has both positive and negative functions on a case-by-case basis in cancer cells (Lin et al 2008). Thus, COX-2 and p53 have an unsteady relationship that can be related to cell growth and apoptosis.…”
Section: Introductionmentioning
confidence: 99%